2008
DOI: 10.1111/j.1365-2249.2008.03705.x
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting human cytokine responses to promastigote whole-cell extract and the Leishmania analogue receptor for activated C kinase antigen of L. amazonensis in natural infection versus immunization

Abstract: SummaryIt is known that the same antigen can induce different immune responses, depending upon the way that it is presented to the immune system. The objective of this study was to compare cytokine responses of peripheral blood mononuclear cells (PBMC) from cutaneous leishmaniasis patients and subjects immunized with a first-generation candidate vaccine composed of killed Leishmania amazonensis promastigotes to a whole-cell promastigote antigen extract (La) and to the recombinant protein LACK (Leishmania analo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…The IL-10 production by PBMC from hCL as well as healthy individuals might be due to the high level of conservation of MAPKK proteins in eukaryotic species. Although MAPKK stimulates high IL-10 levels, it could constitute a potential vaccine candidate since it was recently reported that the human immune response to crude and defined Leishmania antigens generated during immunization can differ from that induced by natural infection (1). Similarly, MAPKK used as a vaccine might induce a dominant Th1 response compatible with protection.…”
mentioning
confidence: 99%
“…The IL-10 production by PBMC from hCL as well as healthy individuals might be due to the high level of conservation of MAPKK proteins in eukaryotic species. Although MAPKK stimulates high IL-10 levels, it could constitute a potential vaccine candidate since it was recently reported that the human immune response to crude and defined Leishmania antigens generated during immunization can differ from that induced by natural infection (1). Similarly, MAPKK used as a vaccine might induce a dominant Th1 response compatible with protection.…”
mentioning
confidence: 99%
“…Both the whole-cell extract of leishmania promastigotes and its supernatant have been indistinctly used as antigenic material in in vitro tests and as pre-clinical and clinical vaccine candidates [ 35 37 ]. Besides, it has been observed that detergent-solubilized proteins of a crude extract of L .…”
Section: Resultsmentioning
confidence: 99%
“…amazonensis and L . braziliensis promastigotes was reported to be more antigenic than the supernatant [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, there are reasons for optimism that one or more safe and effective vaccines against leishmaniasis might be developed ( 3 , 5 , 6 ). A number of parasite antigens have been identified as candidates for vaccine development ( 5 ), including Leishmania analog receptor for activated C kinase (LACK) ( 7 ). Leishmania -activated C-kinase antigen (LACK) is a 36 kDa protein highly conserved across Leishmania species, and is expressed by both promastigotes and amastigotes ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Leishmania -activated C-kinase antigen (LACK) is a 36 kDa protein highly conserved across Leishmania species, and is expressed by both promastigotes and amastigotes ( 8 ). LACK antigen from Leishmania braziliensis, Leishmania guyanensis , and Leishmania amazonensis induces the production of IFN-γ and IL-10 in peripheral blood mononuclear cells (PBMC) from patients with cutaneous leishmaniasis (CL), and IL-10 in those of naïve individuals ( 7 , 9 12 ). LACK drives the expansion of IL-4 secreting T cells ( 13 ), and for that reason LACK vaccination trials used approaches, like cytokines or DNA vectors, to redirect early IL-4 responses to a protective Th1 response ( 14 , 15 ).…”
Section: Introductionmentioning
confidence: 99%